2016
DOI: 10.1111/bjd.14921
|View full text |Cite
|
Sign up to set email alerts
|

Impact of systemic alitretinoin treatment on skin barrier gene and protein expression in patients with chronic hand eczema

Abstract: Our data indicate that the expression of barrier genes and proteins was normalized following treatment with alitretinoin in patients with CHE. The change in expression levels of these genes correlated with the clinical efficacy, suggesting that alitretinoin exhibits a disease-modifying activity. TSLP is upregulated in CHE and seems to counteract filaggrin expression in the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
1
13
2
1
Order By: Relevance
“…The pathogenesis of HHE remains largely unclear. A previous study on the gene and protein expression of hand eczema, including 15 patients with chronic hyperkeratotic‐fissured hand eczema showed, among others, increased proliferative cell activity indicated by Ki‐67, and a decreased expression of the terminal differentiation marker loricrin in palmar lesional skin biopsies, which was normalised following alitretinoin treatment 8 . Another study showed an upregulation in keratinocyte host defence mechanism proteins (S100A7/S100A8/S100A9) in six patients with chronic hand eczema, including different subtypes, compared to healthy control skin 9 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The pathogenesis of HHE remains largely unclear. A previous study on the gene and protein expression of hand eczema, including 15 patients with chronic hyperkeratotic‐fissured hand eczema showed, among others, increased proliferative cell activity indicated by Ki‐67, and a decreased expression of the terminal differentiation marker loricrin in palmar lesional skin biopsies, which was normalised following alitretinoin treatment 8 . Another study showed an upregulation in keratinocyte host defence mechanism proteins (S100A7/S100A8/S100A9) in six patients with chronic hand eczema, including different subtypes, compared to healthy control skin 9 .…”
Section: Discussionmentioning
confidence: 91%
“…A previous study on the gene and protein expression of hand eczema, including 15 patients with chronic hyperkeratotic-fissured hand eczema showed, among others, increased proliferative cell activity indicated by Ki-67, and a decreased expression of the terminal differentiation marker loricrin in palmar lesional skin biopsies, which was normalised following alitretinoin treatment. 8 Another study showed an upregulation in keratinocyte host defence mechanism proteins (S100A7/S100A8/S100A9) in six patients with chronic hand eczema, including different subtypes, compared to healthy control skin. 9 A study on protein expression in seven patients with HHE, showed also increased proliferative cell activity indicated by Ki-67 and a strong upregulation of keratin (K)16 with, in addition, a decreased expression of loricrin in lesional palmar skin compared to perilesional skin and healthy control skin.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the skin endogenously produces substantial amounts of RA and its precursors (such as retinol) that contribute to the maintenance of skin homeostasis [16], while therapeutically applied retinoids represent approved (topical or oral) treatments for a wide range of skin disorders including psoriasis, acne, photoaging, non-melanoma skin cancer, cutaneous T-cell lymphomas, ichthyosis, as well as chronic hand eczema, and they even form part of cosmetic products [17,18,19,20,21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…A tight association between the retinoid system and the skin is underscored by the amounts of RA and its precursors found in this organ and the abundance of proteins involved in RA metabolism and function [15,16], and further substantiated by the broad therapeutic use of retinoids for skin disorders; in fact, retinoid based therapies are inclined towards dermatological conditions [17,18,19,20,21,22,23,24]. …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kumari et al ., 2016, provided immunohistological evidence that treatment with alitretinoin increased the expression of skin barrier proteins that correlated with clinical improvement of chronic hand eczema. They suggested that the improvement was via direct alitretinoin stimulation of keratinocyte proliferation and differentiation and indirectly through reducing inflammatory cytokines produced by infiltrating T cells …”
Section: Discussionmentioning
confidence: 99%